2017
DOI: 10.18632/oncotarget.14472
|View full text |Cite
|
Sign up to set email alerts
|

2017 update on the relationship between diabetes and colorectal cancer: epidemiology, potential molecular mechanisms and therapeutic implications

Abstract: Worldwide deaths from diabetes mellitus (DM) and colorectal cancer increased by 90% and 57%, respectively, over the past 20 years. The risk of colorectal cancer was estimated to be 27% higher in patients with type 2 DM than in non-diabetic controls. However, there are potential confounders, information from lower income countries is scarce, across the globe there is no correlation between DM prevalence and colorectal cancer incidence and the association has evolved over time, suggesting the impact of additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
146
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(163 citation statements)
references
References 298 publications
(274 reference statements)
3
146
2
Order By: Relevance
“…Prospective studies and subsequent meta-analysis have suggested a strong link between DM and CRC (OR 1.27; 95% CI 1.21–1.34) [5053]. It is widely believed that shared risk factors such as increasing age, obesity, high fat diet, sedentary lifestyle, and alcohol and tobacco use all play a role between diabetes and CRC [5456].…”
Section: Treatment Considerations In Diabetes-related Enteropathic DImentioning
confidence: 99%
See 3 more Smart Citations
“…Prospective studies and subsequent meta-analysis have suggested a strong link between DM and CRC (OR 1.27; 95% CI 1.21–1.34) [5053]. It is widely believed that shared risk factors such as increasing age, obesity, high fat diet, sedentary lifestyle, and alcohol and tobacco use all play a role between diabetes and CRC [5456].…”
Section: Treatment Considerations In Diabetes-related Enteropathic DImentioning
confidence: 99%
“…A recent comprehensive review by González et al focused on potential therapeutics for specific molecular mechanisms that address both cancer and DM such as 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMGCoa) reductase inhibitors, renin-angiotensin-aldosterone system (RAAS) targeting (i.e., angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs)), vitamin D receptor (VDR) activators, endothelin receptor antagonists such as atrasentan, anti-fibrotic agents such as anti-CTFG mAb FG3019 and anti-TGF-B1 mAb, anti-inflammatory agents such as chemokinetargeting agents and JAK/STAT inhibitors), epidermal growth factor inhibitors, and mTOR inhibitors [53]. …”
Section: Treatment Considerations In Diabetes-related Enteropathic DImentioning
confidence: 99%
See 2 more Smart Citations
“…However, the biological mechanisms behind metabolism and CRC are complex, and may involve several pathways, such as energy sensing pathways (e.g. AMPK, Sirt1, and mTOR signaling) and the gut microbiome . Therefore, any mediation we observed does not necessarily identify C‐peptide, sOB‐R, and adiponectin as the causal agents driving associations between adiposity and CRC risk, but rather more likely represents the possible importance of metabolism and insulin response as key pathways linking adiposity with CRC risk.…”
Section: Discussionmentioning
confidence: 85%